A Review of Statistical Method for Hypothesis Testing - Sharma, Sunita (AG Volumes, 2025)
In the context of research initiatives, hypothesis testing is an essential component of statistical analyses. It entails estimating the probability of an event occurring by coincidence. In this article review the various literature’s study on statistical method for hypothesis testing. In conclusion, this review highlights the enduring popularity of Null Hypothesis Significance Testing (NHST), despite growing awareness of its limitations. While disciplines like psychology and statistics show stable use, NHST remains widely adopted. Nonparametric methods offer flexible alternatives when assumptions of parametric tests are unmet. The importance of multiple testing correction, careful model selection, and transparent reporting is emphasized to ensure validity and reproducibility. Researchers should move beyond sole reliance on p-values, incorporating confidence intervals and contextual relevance. Advancing statistical literacy and methodological rigor is essential for enhancing the quality and impact of hypothesis-driven research across diverse fields.